2006
DOI: 10.1007/s10620-006-9297-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Probiotics and Nutrients in Functional Gastrointestinal Disorders: A Preliminary Clinical Trial

Abstract: The purpose of this study was to evaluate the efficacy and safety of commonly used probiotics and nutrients available for functional gastrointestinal disorders (FGID). Five different combinations of probiotics and nutrients, or placebo, were taken daily over 12 weeks. In this randomized controlled clinical trial, men and women 21 to 72 years of age with FGID symptoms of indigestion, bloating, and abdominal discomfort were assigned to one of six groups, 12 patients per group. Gastrointestinal Quality of Life In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Overall, of the 13 selected studies, 11 comparisons (79%) reported probiotic benefits on the symptoms of GERD, whereas no benefit was seen in the three remaining comparisons [32][33][34]. Of the 11 former comparisons, five (45%) reported benefits for reflux symptoms, versus five (45%) for dyspepsia symptoms and nine (81%) for other upper-GI symptoms, such as nausea, abdominal pain, and gas-related symptoms (belching, gurgling, burping).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, of the 13 selected studies, 11 comparisons (79%) reported probiotic benefits on the symptoms of GERD, whereas no benefit was seen in the three remaining comparisons [32][33][34]. Of the 11 former comparisons, five (45%) reported benefits for reflux symptoms, versus five (45%) for dyspepsia symptoms and nine (81%) for other upper-GI symptoms, such as nausea, abdominal pain, and gas-related symptoms (belching, gurgling, burping).…”
Section: Resultsmentioning
confidence: 99%
“…A preliminary clinical study exists which investigates the efficacy of probiotics in combination with FvA in gastrointestinal (GI) disorders [ 44 ]. Unfortunately though, all groups including ones with FvA see no improvement in Gastrointestinal Quality of Life Index (GIQLI) and Visual Analogue Scale (VAS) scores for GI symptoms.…”
Section: Gut Healthmentioning
confidence: 99%
“…One of the methods for monitoring is the GIQLI questionnaire [11]. Moreover, the GIQLI has been used for nutrition and QOL assessment in colorectal cancer [12] and functional gastrointestinal disorders [13].…”
Section: Discussionmentioning
confidence: 99%